2021
DOI: 10.3847/1538-4357/abf1e1
|View full text |Cite
|
Sign up to set email alerts
|

Microinstabilities in the Transition Region of Weak Quasi-perpendicular Intracluster Shocks

Abstract: Microinstabilities play important roles in both entropy generation and particle acceleration in collisionless shocks. Recent studies have suggested that in the transition region of quasi-perpendicular (Q ⊥ ) shocks in the high-beta (β = P gas /P B ) intracluster medium (ICM), the ion temperature anisotropy due to the reflected-gyrating ions could trigger the Alfvén ion cyclotron (AIC) instability and the ion-mirror instability, while the electron temperature anisotropy induced by magnetic field compression cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Berezhko et al 2009;Morlino et al 2009;Yuan et al 2012). PIC simulations of SNR shocks suggest that, at high obliquity, electrons drive upstream turbulence prior to ions significant acceleration: again, fully kinetic simulations are needed to determine ion energy spectra (Bohdan et al 2020;Kim et al 2021). We note that low Mach number (∼ 2 − 4) shocks in galaxy clusters (Vazza et al 2015) are also consistent with the near-equipartitioning of (relativistic) electrons and protons or electron acceleration efficiency exceeding protons (K down e/p ∼ 1 − 100).…”
Section: Electron-to-proton Ratiomentioning
confidence: 68%
See 1 more Smart Citation
“…Berezhko et al 2009;Morlino et al 2009;Yuan et al 2012). PIC simulations of SNR shocks suggest that, at high obliquity, electrons drive upstream turbulence prior to ions significant acceleration: again, fully kinetic simulations are needed to determine ion energy spectra (Bohdan et al 2020;Kim et al 2021). We note that low Mach number (∼ 2 − 4) shocks in galaxy clusters (Vazza et al 2015) are also consistent with the near-equipartitioning of (relativistic) electrons and protons or electron acceleration efficiency exceeding protons (K down e/p ∼ 1 − 100).…”
Section: Electron-to-proton Ratiomentioning
confidence: 68%
“…High-amplitude and high-frequency whistler waves excited by electrons in the shock layer (Katou & Amano 2019;Amano et al 2020) and traveling upstream might also drive upstream turbulence. A number of electron-scale instabilities in the high plasma beta regime of intra-cluster shocks were studied in 2D PIC (Kim et al 2021), suggesting that ion-scale waves are generated by distinct instabilities on longer time scales, partially overlapping with electron time scales. Figure 6 shows the ratio of the downstream enthalpy flux of energized particles to the total downstream enthalpy flux as a function of M f .…”
Section: Energetic Particle Fractionsmentioning
confidence: 99%
“…The numerical scheme considered in this work can be applicable to study, e.g., electron acceleration at Earth's bow shock and ion acceleration at a propagating CME-driven shock as well. Note that PIC simulations of low Mach number shocks (e.g., Kim et al 2021) have shown that instabilities can generate small-scale structures that also lead to electron energization. In our work, however, we focus only on DSA.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, two types of electron preacceleration mechanisms have been proposed: (1) the socalled Fermi-like SDA due to multiple cycles of SDA and diffusive scattering of electrons between the shock ramp and upstream self-generated waves (Guo et al 2014a;Kang et al 2019), and (2) the SSDA due to the extended gradient-drift of electrons, while being confined in the shock overshoot (Niemiec et al 2019;Ha et al 2021;Kobzar et al 2021). Reflected particles result in the ion and electron temperature anisotropies, which in turn excite multi-scale plasma waves via various microinstabilities: e.g., the electron firehose instability in the upstream region (Guo et al 2014b;Kim et al 2020), the Alfvén ion cyclotron and ion-mirror instabilities, and the electron whistler and electron-mirror instabilities in the shock overshoot (e.g., Katou & Amano 2019;Kim et al 2021).…”
Section: Introductionmentioning
confidence: 99%